ISLAMIC EDUCATION AND RELIGIOUS MODERATION - Ahmad Fauzi Ilyas; Irvan Mangunsong; Eka Pristiawan; Lahmuddin Lubis (LP2M IAI Al-Khairat Pamekasan, 2026)
This study explores the views of Islamic Religious Education on religious moderation and describes the understanding of religious moderation by three Islamic Religious Education teachers at an Islamic school in Indonesia in August 2025. Religious moderation is seen as an important approach to dealing with multicultural social dynamics. The method used is qualitative with snowball sampling technique for informant selection. Data were collected through in-depth interviews and observations of classes and relevant school activities. The findings show that teachers interpret religious moderation as a principle of balance between commitment to faith and tolerance, as well as social behavior that respects diversity. The implementation of religious moderation in learning practices shows a variety of strategies, such as contextual discussions, case studies of tolerance, and the integration of moderate values into teaching materials. This article proposes recommendations to strengthen the Islamic Religious Education curriculum that favors the formation of moderate attitudes, as well as the development of professional training for teachers. The implications of this research are relevant for Islamic education policymakers and curriculum practitioners.